Hubungan Antara pengelolaan BUMDes Bulu Pala dengan Perrumbuhan Ekonomi lokal di Desa Taulan kec. Cendan kab. Enrekang - adinda Dinda; Darmawan Darmawan; Fitriyani Syukri; Yadi Arodhiskara; Ruslang T (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study aims to empirically examine the relationship between the management of the Village-Owned Enterprise (BUMDes) Bulu Pala' and local economic growth in Taulan Village, Cendana Subdistrict, Enrekang Regency. This research adopted a quantitative approach with a survey method. Data were gathered from 87 community respondents using a Likert-scale questionnaire, supplemented by interviews and documentation. Data analysis techniques included validity, reliability, normality tests, and Pearson correlation analysis performed via SPSS version 25. The results indicate a positive and significant relationship between BUMDes management and local economic growth, with a correlation coefficient (r) of 0.443 and a significance value of 0.000. The strength of this relationship falls into the moderate category, signifying that the contribution of BUMDes governance to the villagers' real economy has not been fully maximized. Based on descriptive analysis, the lack of solid internal coordination among managers and disorderly financial reporting serve as the root problems that weaken institutional supervision. Consequently, the utilization of village capital and resources remains inefficient, causing the presence of BUMDes to be unable to expand new job opportunities significantly in Taulan Village.